Pengaruh Kurs, Uang Elektronik Dan Ekspor Terhadap Inflasi Di Indonesia Tahun 2014-2024 - Adila Sartika Batubara; Hilmiatus Sahla (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study aims to analyze the influence of Exchange Rate, Electronic Money, and Exports on Inflation in Indonesia, both partially and simultaneously. The analysis method used is multiple linear regression with hypothesis testing using the t test (partial) and F test (simultaneous). The results of the partial study indicate that the Exchange Rate does not have a significant effect on Inflation in Indonesia, as evidenced by a probability value of 0.0693 > 0.05. Meanwhile, Electronic Money has a significant negative effect on Inflation with a probability value of 0.0003 < 0.05, which indicates that the increase in the use of electronic money contributes to a decrease in inflation. The Export variable also has a significant positive effect on Inflation with a probability value of 0.0236 < 0.05, which indicates that increased exports have an impact on increasing inflation. Simultaneously, the results of the F test show that the Exchange Rate, Electronic Money, and Exports together have a significant effect on Rupiah Inflation in Indonesia, with a calculated F value of 8.737725 > F table 2.845 and a probability value of 0.000140 < 0.05.